Molecular Evidence for Natural Hybridization between Cotoneaster dielsianus and C. glaucophyllus - Li, Mingwan; Chen, Sufang; Zhou, Renchao; Fan, Qiang; Li, Feifei; Liao, Wenbo (Frontiers in Plant Science, 2017)
Hybridization accompanied by polyploidization and apomixis has been demonstrated as a driving force of evolution and speciation in many plants. A good example to study the evolutionary process of hybridization associated with polyploidy and apomixis is the genus Cotoneaster (Rosaceae), which includes about 150 species, most of which are polyploid apomicts. In this study, we investigated all the Cotoneaster taxa distributed in a small region of Malipo, Yunnan, China. Based on the morphological characters, four Cotoneaster taxa were identified and sampled: C. dielsianus, C. glaucophyllus, C. franchetii, and a putative hybrid. Flow cytometry analyses showed that C. glaucophyllus was diploid, while the three other were tetraploid. Totally five low-copy nuclear genes and six chloroplast regions were sequenced to validate status of the putative hybrid. Sequence analyses showed C. dielsianus and C. glaucophyllus are distantly related, they could be well separated by totally 50 fixed nucleotide substitutions and four fixed indels at the 11 investigated genes. All the individuals of the putative hybrid harbored identical sequences: they showed chromatogram additivity for all the fixed differences between C. dielsianus and C. glaucophyllus at the five nuclear genes, and were identical with C. glaucophyllus at the six chloroplast regions. Haplotype analysis revealed C. dielsianus possessed nine haplotypes for the 11 genes, while C. glaucophyllus had ten, and there was no shared haplotypes between the two species. The putative hybrid harbored two haplotype for each nuclear gene: one was shared with C. dielsianus and the other with C. glaucophyllus. They possessed the same chloroplast haplotype with C. glaucophyllus. Our study provided convincing evidence for natural hybridization between C. dielsianus and C. glaucophyllus, and revealed that all the hybrid individuals were derivatives of one initial F1 via apomixis, and C. glaucophyllus served as maternal parent at the initial hybridization event. We proposed that anthropological disturbance provided an opportunity for hybridization between C. dielsianus and C. glaucophyllus, and a tetraploid F1 successfully bred many identical progenies via apomixis. Under this situation, species integrity could be maintained for these Cotoneaster species, yet attentions should be kept for this new-born hybrid.